The Potential for Topical Probiotic Treatment of Chronic Rhinosinusitis, a Personal Perspective - Cervin, Anders U. (Frontiers in Cellular and Infection Microbiology, 2018)
This review describes the rationale for topical probiotic intervention, the obstacles we are facing and a strategy for future research in the use of probiotics to modify CRS symptoms and disease expression. Recent advances in molecular microbiology has revealed a plethora of microbial DNA in the nasal cavity and sinuses of healthy subjects as well as in chronic sinusitis (CRS) patients. An infection is today rather seen as an imbalance between the commensal microbiome and the bacterial pathogens, resulting in a reduction in commensal bacterial diversity, combined with an increase in the growth of microbes eliciting an inflammatory response. This will in turn lead to the clinical symptoms of sinusitis. Probiotics (microorganisms that confer a health benefit) can be used either as a form of living antibiotics treatment, or as an immune-modulatory intervention. Topical probiotics, which is the focus of this review, have shown efficacy in a limited number of trials in otitis media and tonsillitis, but to date not in CRS. Although bacterial interference capacity against pathogens can be determined in in vitro experiments, it may not translate to a health benefit. This limits the role of laboratory research in identifying probiotic strains with a clinical benefit. To gain more clinical experience without further delay, I recommend future research to focus on empirical clinical trials in well-defined CRS patient populations and study the underlying mechanisms in more detail once a clinical benefit has been established